Dinuclear and polymeric Hg(II) complexes with 1-(2-furoyl)thiourea derivatives: Their crystal structure and related properties. (5th September 2015) - Estévez-Hernández, O.; Duque, J.; Rodríguez-Hernández, J.; Reguera, E.
Graphical abstract: Dimeric and polymeric complexes were prepared by reaction of HgCl2 with 1-(2-furoyl)thiourea derivatives in ethanol. Their structures were determined from X-ray powder diffraction data using direct space global optimization strategy (simulated annealing) followed by the Rietveld refinement. Abstract: Dimeric and polymeric complexes bis{[(1-(2-furoyl)-3-bencyl-3-phenylthiourea-κS)chloromercury(II)]-μ-chloro} (HgCl2 -FBFT ) and catena -poly{[(1-(2-furoyl)-3-bencylthiourea-κS)chloromercury(II)]-μ-chloro} (HgCl2 -FBT ) were prepared by reaction of HgCl2 with 1-(2-furoyl)-3-bencyl-3-phenylthiourea (FBFT ) and 1-(2-furoyl)-3-bencylthiourea (FBT ) in ethanol. Their crystal structures were solved and refined from X-ray powder diffraction data using direct space global optimization strategy (simulated annealing) followed by the Rietveld refinement. Both solids exhibit 1:1 metal:ligand stoichiometry and a distorted tetrahedral geometry for the coordination mercury centers. The mercury(II) complexes were characterized by elemental analysis, Raman, NMR and TG-DTG data. ComplexHgCl2 -FBFT crystallizes in the triclinic system, space group P 1 ¯, whileHgCl2 -FBT crystallizes in the orthorhombic system, space group Pcnn . In the dimeric complexHgCl2 -FBFT each Hg(II) atom is found coordinated to S atom of ligand, and to a terminal and two bridging chlorine atoms. Neighboring dimers remain together in the solid through dipolar and quadrupolar interactions. The complexHgCl2 -FBT is a polymer of mercury(II) bridged to two chlorine ions and also coordinated by terminal chlorine ion and a molecule of ligand through the S atom. This compound exhibits intramolecular and intermolecular hydrogen bonds; these last ones are responsible for packing of the polymeric chains in a 3D framework. The photoluminescence properties indicate that both complexes are fluorescent materials with maximum emission at 425 nm.